O brinquedo e a imaginação da terra: um estudo das brincadeiras do chão e suas interações com o elemento fogo - Aires, Jouberth Gandhy Maranhão Piorski (2013)
This paper investigates the symbolic matrices listed in the practices of play. The toy built by the child proposes a planning, tutoring inherent energy to the deep layers of imagery and dialogue with a wide field of archaic experiences of the traditional man. Entering the free play in the territory of the great images in the formulations of the noumenal imagination. Having as foundation philosophy of pictures of Gaston Bachelard and symbolic hermeneutics, opened this proposition investigative around life playful childhood. From Bachelard's idea of the four elements, work with the earth element in the investigation of the practices of the child in traditional communities linked to the natural world. Investigate together the confluences and imaginary impressions with the fire element. When imagination sustains fire from the earth to forge births in the center of the game. Points, so our study to construct a social therapy germinated in play.